DIVERSIFIKASI MODEL CAREER PATH PROGRESSION BAGI PUSAT PENGEMBANGAN KARIR DI UIN ALAUDDIN MAKASSAR - Aulia Rahman B; Ahmad Kafrawi Mahmud (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
This study describes new adaptations in student career planning for career managers in higher education. Diversification of career path progression models needs to be developed in universities to answer public doubts about the quality of alumni of the State Islamic Religious College to compete in the world of work. The type of research used is research and development (R&D). In the preliminary field testing stage, quite good results were obtained with various counseling methods. Students' perceptions of the first trial were 79.20 percent said they were confident in registering with a well-known company after going through this program. After the operational field testing stage, it gives us confidence that the talent mapping model that has been used to see the potential and map employees in companies can be adapted for career planning at UIN Alauddin Makassar and become a prototype for career development at State Islamic Religious College.